The oxidation mechanism of 3, 4-dihydroxy-2-butanone in the aqueous phase for secondary organic aerosols formation. (15th January 2020) - Xu, Luyao; Lv, Guochun; Liu, Wen; Sun, Xiaomin; Zhang, Chenxi; Li, Zhiqiang
Abstract: 3, 4-dihydroxy-2-butanone (DHBO) is a major oxidation product of IEPOX and can easily be oxidized in tropospheric aqueous phase. The aqueous oxidation mechanism of DHBO has investigated by DFT and initial reaction rate constants also have calculated through TST. In the aqueous phase, the following trend in reactivity of initial reaction can be obtained: OH ≫ SO4 − > NO3, which bases on the calculated rate constants ( k (OH) = 1.20 × 10 8 L mol −1 s −1, k (SO4 − ) = 8.51 × 10 5 L mol −1 s −1 and k( NO3 ) = 2.86 × 10 5 L mol −1 s −1 ) at 298 K and 1 atm. After initial reaction, the major products of DHBO further react with OH radical at presence of O2. The final products include acetic acid and methylglyoxal, which are important SOA precursors. This work provides a reference for oxidation mechanism of dihydroxycarbonyl of isoprene-driven in aqueous and help understand SOA formation. Graphical abstract: Image 1 Highlights: The aqueous oxidation mechanism of DHBO has been studied. The OH. -initiated reaction rate constant is 1.20 × 10 8 L mol −1 s −1 at 298 K and 1 atm. Acetic acid and methylglyoxal of main products contribute to aqSOA formation. The HO2 and RO2 of minor products increase the ozone yield.